Gambling in America : costs and benefits - Grinols, Earl L., 1951- (Cambridge University Press, 2004)
Gambling in America carefully breaks new ground by developing analytical tools to assess the benefits and costs of the economic and social changes introduced by casino gambling in monetary terms, linking them to individual households' utility and well-being. Since casinos are associated with unintended and often negative economic consequences, these factors are incorporated into the discussion. The book also shows how amenity benefits - for casinos, the benefit to consumers of closer proximity - enter the evaluation. Other topics include agent incentives and public decision making, conceptual clarifications about economic development, cost-benefit analysis, and net export multiplier models. Professor Grinols finds that, in considering all relevant factors, the social costs of casino gambling outweigh their social benefits.